Data-driven MPC of descriptor systems: A case study for power networks. Issue 30 (2022) - Schmitz, Philipp; Engelmann, Alexander; Faulwasser, Timm; Worthmann, Karl
Abstract: Recently, data-driven predictive control of linear systems has received wide-spread research attention. It hinges on the fundamental lemma by Willems et al. In a previous paper, we have shown how this framework can be applied to predictive control of linear time-invariant descriptor systems. In the present paper, we present a case study wherein we apply data-driven predictive control to a discrete-time descriptor model obtained by discretization of the power-swing equations for a nine-bus system. Our results show the efficacy of the proposed control scheme and they underpin the prospect of the data-driven framework for control of descriptor systems.